The Lychee Erinose Mite Aceria litchii (Keifer) (Acari: Eriophyidae) - Alexandra M. Revynthi; Jonathan H. Crane; Jeff Wasielewski; Paul E. Kendra; Daniel Carrillo (EDIS)
The lychee erinose mite is an important pest of lychee and is found in lychee-producing countries in Asia and South America and in Australia, Hawaii, and Brazil, where it has has caused an estimated 70–80% yield reduction and a 20% increase in production costs. Found in Lee County, Florida, in 2018, it has since spread to several counties in central and south Florida. The Florida Department of Agriculture and Consumer Services , Division of Plant Industry established an eradication program and a quarantine in Lee county. Management in other countries includes chemical control in combination with pruning. The purpose of this publication is to provide an in-depth profile of the lychee erinose mite. It is intended for the use of interested laypersons with some knowledge of biology as well as academic audiences.